Numerical and Religious-Based School Management Training to Support the Vision-Mission of Educational Institutions - Mohammad Faizal Amir; Muhlasin Amrullah; Machful Indrakurniawan (Universitas Lambung Mangkurat, 2022)
School management focuses on achieving educational goals and visions. In reality, the school's vision mission is not on needs but only used during accreditation. This happened at SDN Legokulon 1 Kasreman; most teachers did not understand school management enough to support the school's vision-mission. Numeracy-based and religious school management training is needed to support a quality school's mission. Training was held at SDN Legokulon 1 Kasreman on 18-19 February 2022. This activity used participatory rural appraisal for training and evaluation. Eight SDN Legokulon 1 Kasreman teachers attended this training. Based on evaluations, 87.5% of participants understood numeracy and religious-based school management. In addition, numeracy and religious-based school management are generally good. So, this training affects SDN Legokulon 1 Kasreman stakeholders' understanding of numeracy and religious-based school management to support the school's vision mission.